An investigation of the tufa deposits at Ga-Mohana Hill in the Northern Cape, South Africa: palaeoenvironmental context for Late pleistocene and holocene human occupation in the Southern Kalahari - von der Meden, Jessica Johanna (Department of Geological Sciences, 2025)
There is a rich record of human occupation in the southern Kalahari, but the palaeoclimatic backdrop to early human activity in this area is poorly understood. Secondary calcium carbonates, including tufa, are common in the Kalahari, yet their palaeoclimate potential remains relatively unexploited. Tufa deposits at Ga-Mohana Hill, an archaeological site in the southern Kalahari, represent past water availability in a presently semi-arid region. Tufa are useful palaeoclimate proxies that form from freshwater springs and streams. They are amenable to radiometric dating, and conditions during their formation can be investigated through geochemical proxies, such as carbon and oxygen isotopes. In this study, I use the tufa deposits at Ga-Mohana Hill, and their association with the archaeological record of Late Pleistocene and Holocene human occupation, to investigate the interplay between environmental changes and human evolution in this previously understudied region. I show that the Ga-Mohana tufa deposits comprise cascade, barrage, terrace breccia and dome morphologies that formed from a presently inactive perched-springline system, and that these represent past streams, waterfalls, and shallow pools. Based on petrographic observations, bulk X-ray diffraction, and in situ laser ablation analysis, calcite is identified as the main crystalline phase, along with variable inclusions of quartz and other non-carbonate phases rich in Mn, Fe and Al. Element distribution maps constructed from laser ablation analysis were used to identify portions of the tufa samples suitable for uranium-thorium dating. Episodic tufa formation over the last ~114 ka is inferred from thirty-three U-Th ages obtained from twelve tufa samples. These episodes are interpreted to indicate water availability during MIS 5d (~114 - 100 ka), MIS 4 (~73-57 ka), two stages during MIS 3 (~57-48 ka, and ~44-32 ka), and two stages during the Holocene (~15 - 6 ka, and ~4-2 ka). This timing supports the notion that conditions for tufa formation are not restricted to warm and wet interglacial periods. The tufa carbon (-8.83 to +3 .55‰) and oxygen (-6.14 to -0.05‰) isotope values indicate some kinetic fractionation effects, likely driven by evaporation. The carbon isotopes indicate a combined input of soil-derived CO2 and heavier bedrock CO2, along with a high proportion of C4 vegetation, except during MIS 4, during which lower d13C values indicate a higher input of soil-derived CO2 and/or a greater proportion of C3 vegetation. Overall, the carbon and oxygen isotope values indicate a gradual increase in aridity over the last ~70 ka, i.e., warmer temperatures, increased evaporation, and a higher proportion of C4 vegetation, albeit wet enough to sustain tufa formation. Three of the tufa episodes coincide with archaeological units at Ga-Mohana Hill, dated to ~105 ka, ~31 ka, and ~15 ka. I propose that prior to ~70 ka, human occupation in the region coincided with water availability, whereas by ~30 ka, water availability was much reduced, yet human occupation persisted. Following the last glacial maximum (LGM) there is evidence of human occupation despite variable water availability at Ga-Mohana Hill, and in the region. This may point to early human development of arid-adaptive behaviours in the southern Kalahari.